Comparative toxicological effects of planktonic Microcystis and benthic Oscillatoria on zebrafish embryonic development: Implications for cyanobacteria risk assessment. (1st April 2021) - Li, Hongmin; Gu, Xiaohong; Chen, Huihui; Mao, Zhigang; Zeng, Qingfei; Yang, Huiting; Kan, Kecong
Abstract: Planktonic and benthic cyanobacteria blooms are increasing in frequency in recent years. Although many studies have focused on the effects of purified toxins or cyanobacteria extracts on fish developments, the more complex impacts of cyanobacteria cells on fish populations are still considered insufficient. This study compared the toxicological effects of harmful planktonic Microcystis and benthic Oscillatoria on zebrafish ( Danio rerio ) early stages of development. Zebrafish embryos, at 1–2 h post fertilization (hpf), were exposed to 5, 10, and 20 × 10 5  cells/mL Microcystis (producing microcystins) or Oscillatoria (producing cylindrospermopsins) until 96 hpf. The results indicated that the effects of benthic Oscillatoria on embryonic development of zebrafish were different from those of planktonic Microcystis . Reduced hatching rates, increased mortality, depressed heart rates and elevated malformation rates were observed following exposures to increased concentrations of Microcystis, whilst Oscillatoria exposures only caused yolk sac edemas. Exposure to a high concentration of Microcystis induced severe oxidative damage, growth inhibition and transcriptional downregulations of genes ( GH, GHR1, IGF1, IGF1rb ) associated with the growth hormone/insulin-like growth factor (GH/IGF) axis. Although Oscillatoria exposure did not affect the body growth, it obviously enhanced the antioxidant enzyme activities of superoxide dismutase (SOD), catalase (CAT) and glutathione peroxidase (GPx) and up-regulated the expressions of several oxidative stress-related genes. Discrepancies in the developmental toxicity caused by Microcystis and Oscillatoria may not only attributed to the different secondary metabolites they secrete, but also to the different adhesion behaviors of algal cells on embryonic chorion. These results suggested that harmful cyanobacteria cells could influence the successful recruitment of fish, while the effects of benthic cyanobacteria should not be ignored. It also highlighted that the necessity for further investigating the ecotoxicity of intact cyanobacterial samples when assessing the risk of cyanobacterial blooms. Graphical abstract: Image 1 Highlights: Microcystis exposure caused growth inhibition and oxidative damage. Disruption of GH/IGF axis contributed to the growth inhibition. Oscillatoria exposure did not influence body growth, but induced oxidative stress. Cyanotoxins alone in the present study cannot fully explain the observed effects. The ecological risks of intact cyanobacterial cells should deserve more attention. Abstract : A brief summary: The toxic effects of harmful cyanobacteria on zebrafish embryonic development are not only related to the known cyanotoxins, but also to the species of cyanobacteria cells.